Fear‐potentiated startle response as an endophenotype: Evaluating metrics and methods for genetic applications. (4th January 2019) - Savage, Jeanne E.; Moore, Ashlee A.; Sawyers, Chelsea K.; Bourdon, Jessica L.; Verhulst, Brad; Carney, Dever M.; Moroney, Elizabeth; Machlin, Laura; Kaabi, Oumaima; Vrana, Scott; Grillon, Christian; Brotman, Melissa A.; et al.
Abstract: The modulation of the startle response (SR) by threatening stimuli (fear‐potentiated startle; FPS) is a proposed endophenotype for disorders of the fearful‐fearlessness spectrum. FPS has failed to show evidence of heritability, raising concerns. However, metrics used to index FPS—and, importantly, other conditional phenotypes that are dependent on a baseline—may not be suitable for the approaches used in genetic epidemiology studies. Here, we evaluated multiple metrics of FPS in a population‐based sample of preadolescent twins ( N = 569 from 320 twin pairs, M age = 11.4) who completed a fear‐conditioning paradigm with airpuff‐elicited SR on two occasions ( 1 month apart). We applied univariate and multivariate biometric modeling to estimate the heritability of FPS using several proposed standardization procedures. This was extended with data simulations to evaluate biases in heritability estimates of FPS (and similar metrics) under various scenarios. Consistent with previous studies, results indicated moderate test‐retest reliability ( r = 0.59) and heritability of the overall SR ( h 2 = 34%) but poor reliability and virtually no unique genetic influences on FPS when considering a raw or standardized differential score that removes baseline SR. Simulations demonstrated that the use of differential scores introduces bias in heritability estimates relative to jointly analyzing baseline SR and FPS in a multivariate model. However, strong dependency of FPS on baseline levels makes unique genetic influences virtually impossible to detect regardless of methodology. These findings indicate that FPS and other conditional phenotypes may not be well suited to serve as endophenotypes unless such codependency can be disentangled. Abstract : This study investigated how commonly used measurement transformations can bias estimates of heritability for some measures that have been proposed as endophenotypes for psychiatric disorders, such as fear‐potentiated startle. Results demonstrated that conditional measures, derived by standardizing or subtracting out a baseline level from a measured response variable, are not suitable for the standard types of heritability analyses typically applied in research. These findings indicate limited applicability of fear‐potentiated startle and other conditional measures as endophenotypes and highlight the need for utilizing appropriate statistical methodology in the study of such measures.